A Griggs apparatus upgrade for stress-controlled testing of geological material at high temperature and pressure. (April 2021) - Soleymani, Hamid; Kidder, Steven
Graphical abstract: Abstract: The Griggs apparatus is a triaxial piston-cylinder instrument used in deformation experiments of geological material at temperatures up to 1200 °C and confining pressures up to 3 GPa. Currently, most Griggs apparatuses can carry out deformation experiments only at constant displacement rate. As a result, few experimental studies have explored other geologically-relevant deformation scenarios. We present supplemental instrumentation and software that enables Griggs apparatus users to carry out deformation experiments at controlled differential stress conditions. The add-on instrument includes a feedback loop mechanism that regulates the imposed differential stress on the sample and a data acquisition system that allows for real-time display of mechanical data in units of stress and displacement. We demonstrate the application of this instrument through two deformation experiments at constant differential stress on (1) an aluminum cylinder at room temperature and (2) a quartz aggregate at 850 °C, both at ~1 GPa confining pressure. These experiments show that the instrument can reliably control the imposed differential stress on the sample throughout the deformation. Applications of the instrument can be extended beyond constant differential stress to more sophisticated stress paths (e.g., stress pulse, stress ramp) or to maintain true strain rates by accounting for anticipated geometrical changes in the sample during deformation.